Rural Drinking Water Supply in Poverty Alleviation Areas in China - Ji Qinghua, Dong Shuoxun, Cao Xiaofeng, Liu Huijuan, Qu Jiuhui (《中国工程科学》杂志社, 2021)
Ensuring the safety of rural drinking water is a basic component of poverty alleviation in China. Studying the strategy for ensuring drinking water safety in areas that were lifted out of poverty is important for consolidating poverty alleviation achievements and promoting rural revitalization in China. In this article, we study the current situation and problems of rural drinking water in poverty alleviation areas, analyze the causes of the problems, and propose strategic objectives and pathways from the aspects of engineering, policy, and mechanism. To guarantee the safety supply of rural drinking water in poverty alleviation areas, we suggest that the drinking water safety policies in these areas should remain stable and constant, the sanitary standards of drinking water in rural areas should be optimized to meet those in urban areas, and a long-term policy focusing on water price should be established for rural water supply.